2016
DOI: 10.3390/w8070296
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Variability in the Water Quality of Poyang Lake and Its Associated Responses to Hydrological Conditions

Abstract: Abstract:Determining the spatiotemporal water quality patterns and their corresponding driving factors is crucial for lake water quality managements. This study analyzed hydrological data and concentrations of 11 water quality parameters, including total nitrogen, total phosphorus, ammonia nitrogen and chlorophyll-a (Chl-a), for water samples collected from 15 sampling sites between 2009 and 2014. The water quality of sites in the northern Poyang Lake-Yangtze River waterway was influenced by different environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 45 publications
3
11
0
Order By: Relevance
“…In shallow lakes with great WLFs, the changes of water quality during a hydrological year were significantly controlled by WLFs (Wantzen et al, 2008; White et al, 2008; Stefanidis and Papastergiadou, 2013). In general, water quality responds immediately to WLFs and was worse with high nutrient concentrations in dry-season than in wet-season, because in dry-season, the lake have a low water capacity for dilution and degradation, low biological consuming of nutrients, and high release of nutrients from sediment to water (Zhu et al, 2013; Yao et al, 2015; Li et al, 2016; Liu X. et al, 2016; Hideo et al, 2017). For PYL particularly, previous studies about the water quality variation associated to WLFs demonstrated high nitrogen concentrations in dry-season (Wu et al, 2006; Yao et al, 2015; Liu X. et al, 2016), compositional changes in DOC related to hydrological regime (White et al, 2008; Yao et al, 2015), and complex distribution patterns of phosphorus (Xiang and Zhou, 2011; Wang and Liang, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In shallow lakes with great WLFs, the changes of water quality during a hydrological year were significantly controlled by WLFs (Wantzen et al, 2008; White et al, 2008; Stefanidis and Papastergiadou, 2013). In general, water quality responds immediately to WLFs and was worse with high nutrient concentrations in dry-season than in wet-season, because in dry-season, the lake have a low water capacity for dilution and degradation, low biological consuming of nutrients, and high release of nutrients from sediment to water (Zhu et al, 2013; Yao et al, 2015; Li et al, 2016; Liu X. et al, 2016; Hideo et al, 2017). For PYL particularly, previous studies about the water quality variation associated to WLFs demonstrated high nitrogen concentrations in dry-season (Wu et al, 2006; Yao et al, 2015; Liu X. et al, 2016), compositional changes in DOC related to hydrological regime (White et al, 2008; Yao et al, 2015), and complex distribution patterns of phosphorus (Xiang and Zhou, 2011; Wang and Liang, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…We attributed the lower contribution of nutrient variation in wet-season to the complex hydrological characteristics. In wet-season, PYL has the highest water level but the lowest velocities due to the large amount of inputs from its five tributaries as well as the backflows of the Changjiang River (Li et al, 2016). Compared to its catchment inflow, the Changjiang River discharge has a greater impact on intra-annual WLFs of PYL (Ye et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, water depth was also found to be the most crucial factor for diatoms local species richness in subarctic streams, while the elevation significantly correlated with community dissimilarity (Teittinen et al, 2016). In Poyang Lake (China), Li et al (2016) found water level as the main controlling factor that controlled the phytoplankton seasonal variability, which actually reflected changes of water quality.…”
Section: Hydrological Factorsmentioning
confidence: 91%
“…According to the method proposed by Li et al [22], the seasonal variation of water quality is analysed using…”
Section: Discussionmentioning
confidence: 99%